The perfect rule of the Christian religion: a history of Sandemanianism in the eighteenth century - Smith, John Howard (SUNY Press, 2008)
I thought myself a sound Presbyterian -- The perfect rule of the Christian religion -- He becomes possessed of a truth -- May God preserve our [churches] amidst all attacks -- Spirited conduct -- Mine eyes must flow with a river of tears